Situative Black Girlhood Reading Motivations: Why and How Black Girls Read and Comprehend Text - Sara Jones (MDPI AG, 2024)
This study aims to illustrate the complex relationships between reading motivation and reading comprehension for Black girl readers. There is an urgent need for research that explicitly centers on the reading motivations of Black girls through a humanizing, asset-oriented lens. Through a Situative Black Girlhood Reading Motivations lens, which integrates a situative perspective on motivation and the tenets of Black Girlhood Studies, this multi-year study focuses on a group of Black girl readers participating in a summer reading program. Qualitative data, including video observations, student work artifacts, and small-group artifact-elicited interviews, were analyzed through a generic inductive approach to answer the research question, "How are relationships between Black girls' reading motivations and their reading comprehension evident in their reading engagement and enactments?" The findings demonstrate that the participants' most salient reading motivations in this instructional context (meaning-oriented, collaborative, and liberatory reading motivations) (1) were a precursor to their comprehension, (2) worked in tandem with their comprehension, and (3) stemmed from their comprehension. These findings contribute to models of reading by illustrating the need for additional complexity when describing the relationship between reading motivation and comprehension.